Synthesis of ultrafine (Mo,W)Si2 composite powders from high purity molybdenum concentrate - Huang J.-B.; Zhang G.-H. (Journal of Mining and Metallurgy. Section B: Metallurgy)
(Mo,W)Si2 composite powders with the grain size of about 1 μm were synthesized at 1150℃ for 2 h. The high purity molybdenum concentrate (with the main component of MoS2), W and Si powders were utilized as raw materials and lime as desulfurizer. The graphite felt was laid between the compact (made of MoS2, W and Si) and the lime to facilitate the separation of the produced composite powders from desulfurization product. The phase composition, microstructure evolution, and residual sulfur content during the silicothermic reduction reaction were evaluated. The experimental results showed that the reaction could be completed after a reaction time of 1150℃ for 2 h, and the residual sulfur content of the product was 0.087 wt.%. It was concluded that the interactions between Si and the intermediate products of SiS and SiS2 are crucial for the preparationof (Mo,W)Si2 composite powders at low temperatures. The preparation process could be divided into three stages: solid state reactions between MoS2, W and Si to produce MoSi2, WSi2 and gaseous SiS; gas-solid reaction between MoS2, W and gaseous SiS to generate MoSi2, WSi2 and gaseous SiS2; and gas-solid reaction between gaseous SiS2 and Si to form SiS gas. With this short flow process, fine-grained (Mo,W)Si2 composite powders can be produced at low cost at low temperature, which has great application potential.